Studies of mitochondrial genomics in Salmo trutta fario - Abolhasan Rezaei; Sheyda Akhshabi (Mitochondrial DNA Part B, 2017)
Salmo trutta fario population is an important species for aquaculture and livestock industry. Moreover, these species were used for studies on the molecular markers. Mitochondrial genomic is also beneficial for phylogenetic studies in salmonid species. They applied maternal traits for mitogenome, whereas paternal traits related to nuclear genomics. It will be genetically highly divergent indicating that they may represent distinct and potentially locally adapted gene pools (Apostolidis et al., 2011). Evolutionary history has been studied on the Salmo taxa such as brown trout, Salmo salar, Salmo trutta populations (Kottelat & Freyhof, 2007; Simonovic et al., 2007).